Kebudayaan Lokal dan Pemberdayaannya - Bambang Hudayana (Jurnal Ilmu Sosial dan Ilmu Politik, 2000)
This paper underlines the importance of local culture as a basis to empowerthe Indonesian society which, during the era globalization and the late of capitalism attempt to engage in a process of reform based on a cultureal diversity. The modernist regime of the New Order has undermined local culture and treat it as he enemy of development and national itegration, so that many local cultures have been weakeningg. Many cases, indeed, show that local culture have played an important role in empowering local people as they provide alternatives for solving the weaknesses of development. Many local cultures have social-political value, and furthermore the have also economic value which can be managed to enhance welfare among the marginal people to actualize their potential, self-esteem, andcreativity became the bases of socio-cultural identity creation among the local people that live the pluralistic and compeetitive system. It is expected that the empowerment of local culture arise in near future as a part of the agenda of regional autonomy, globalization and late capitalism era. The process of empowerment will strengthen the spririt of pluralism and national solidarity.